A review of the wasp mimicking spider genus Coenoptychus Simon, 1885 (Araneae: Corinnidae: Castianeirinae) - Paul, Jimmy; Sankaran, Pradeep M.; Sebastian, Pothalil A.; Joseph, Mathew M. (Zootaxa, 2018)
The monotypic velvet ant-mimicking spider genus Coenoptychus Simon, 1885 is revised. The paper provides the first detailed morphological and genitalic description, with the first description and illustrations of the male of the type species, Coenoptychus pulcher Simon, 1885, and a redescription of its female. Two new combinations are proposed: Coenoptychus mutillicus (Haddad, 2004) comb. nov. and Coenoptychus tropicalis (Haddad, 2004) comb. nov.; both species were previously included in Graptartia Simon, 1896. The distribution records of the genus are updated.